New horizons in geriatric medicine education and training: the need for pan-European education and training standards - Fisher, James M.; Masud, Tahir; Holm, E.A.; Roller-Wirnsberger, Regina; Stuck, A.E.; Gordon, Adam L.; Blain, H.; Knight, Paul; Fruhwald, Thomas; Petermans, J.; Nuotio, M.S.; Ihle-Hansen, H.B.; et al. (Elsevier, 2017)
The ageing population ought to be celebrated as evidence for the efficacy of modern medicine, but the challenge that this demographic shift presents for 21st century healthcare systems, with increasing numbers of people living with multi-morbidity and frailty, cannot be ignored. There is therefore a need to ensure that all healthcare professionals grasp the basic principles of care of older people. In this paper, we make a case for the development of pan-European education and training standards for the field of geriatric medicine. Firstly, the challenges which face the implementation and delivery of geriatric medicine in a systematic way across Europe are described – these include, but are not limited to; variance in geriatric medicine practice across Europe, insecurity of the specialty in some countries and significant heterogeneity in geriatric medicine training programs across Europe. The opportunities for geriatric medicine are then presented and we consider how engendering core geriatric medicine competencies amongst nongeriatricians has potential to bridge existing gaps in service provision across Europe. Finally, we consider how work can proceed to teach sufficient numbers of doctors and health professionals in the core knowledge, skills and attitudes required to do this. To safeguard the future of the specialty across Europe, we contend that there is a need to strive towards harmonisation of post-graduate geriatric medicine training across Europe, through the establishment of pan-European education and training standards in the specialty.